Wideband sound absorption of 3D printed multi-layer micro-perforated panels - Yang, Wenjing (2018)
Micro-perforated panel (MPP) absorbers have been applied widely in noise reduction and sound damping. In order to obtain wideband sound absorption, novel structures of MPPs with various numbers of panel layers and spacing distances between them were designed. The structures were manufactured by selective laser sintering, which is an advanced 3D printing technique producing complex structures effectively. The sound absorption coefficients of MPPs were measured by the impedance tube method. The results suggested that the multi-layer structures significantly increased the bandwidths of the absorption compared to the single-layer MPPs. This research work demonstrates the large potential of artificial acoustic designs of MPP via 3D printing for wideband absorption through controlling the layer number and the spacing distance.